Bioavailabilitas Mineral Ca (in vitro) pada Jagung (Zea mays L), dengan Penambahan Asam Sitrat dan Fitase Bacilus subtilis HG - Yulia Ratri Kurniawati (Jurnal Kesehatan Islam : Islamic Health Journal, 2021)
Abstract. Background & Aims: Mineral Ca is the most abundant mineral in the human body. Lack of mineral Ca in the human body in the long term will result in loss and calcification. Corn is food ingredient that contains vegetable calcium, it is widely consumed by Indonesians. The purpose of the research to obtain information on the bioavailability of the mineral Ca (in vitro) in corn (Zea mays L) with the addition of citric acid and phytase’s Basillus subtilis HG isolate.Methods: The research consists of two steps. The first step is to determine the best treatment in reducing phytate acid in corn with variations of the submersion duration and the citric acid concentrate, with the variation of phytase enzyme concentrations. The second step is to determine the bioavailability of mineral Ca through in vitro proses. The data analysis used two way anova and one away anova.Results: The results of the research: 1) the best treatment to reduce phytate acid in found in the immersion of corn with 9% citric acid for 12 hours in the amount of 32.45%, whereas in the variation of the concentration of phytase enzyme 250µL/50mL in the amount 50.09%. 2) The highest bioavailability of mineral Ca through in vitro is in amount of 56.880% with 9% citric acid for 12 hours and with the increment of phytase enzyme 250µL/50mL.Conclusion: The increase in bioavailability of mineral Ca in corn (Zea mays L) was influenced by the addition of citric acid concentration, submersion duration, and the concentration of phytase enzyme. Research on mineral bioavailability can be further developed by examining other foodstuffs containing phytate acid, and carried out by more sophisticated methods and analyzed, and the methods that have been done can be used to study the degradation of phytate to other bivalent minerals.